Thermal degradation kinetics of bioactive compounds from black rice flour (Oryza sativa L.) extracts. (September 2016) - Bolea, Carmen; Turturică, Mihaela; Stănciuc, Nicoleta; Vizireanu, Camelia
Abstract: The effect of thermal processing on the degradation of the phytochemicals in black rice flour by means of fluorescence spectroscopy and degradation kinetics was investigated. In order to investigate the influence of food matrices, a comparative analysis between integral rice flour and different fractions was performed. The preliminary compositional results suggested a higher content in phytochemicals in fraction four of the seven fractions of black rice flour, which was sifting through a sieve with a diameter of 180 μm. The compositional complexity was highlighted by fluorescence spectroscopy. The heat-treatment caused structural changes that led to red- or blue-shifts in maximum emission. The first-order kinetic model was used to describe the mechanism of degradation. The activation energies were 10.07 ± 1.04 kJ/mol for total polyphenolic, 7.26 ± 0.58 kJ/mol for total monomeric anthocyanins and 6.71 ± 1.12 kJ/mol for antioxidant activity in case of integral flour extract. For fraction four extract obtained by, the E a values were: 3.51 ± 0.53 kJ/mol, 11.49 ± 1.47 kJ/mol, 15.80 ± 1.50 kJ/mol and 19.91 ± 3.27 kJ/mol, respectively. The calculated values of the activation energy revealed higher temperature dependence of total polyphenols in integral flour and of antioxidant activity in fraction four, respectively. Highlights: Impact of thermal treatment on phytochemicals was investigated. Fluorescence spectroscopy suggested heat-induced red- or blue-shifts in maximum emission. A protective effect of whole flour on anthocyanins and flavonoids was found. An accelerated degradation of polyphenols in the integral flour was observed.